Assessment of Private Homes as Spaces for the Dying Elderly - Bhattacharyya, Tulika (Indian J Palliat Care, 2017)
AIM: This study makes an assessment of end-of-life care of the elderly in private homes in Kolkata, West Bengal, India. PARTICIPANTS AND METHODS: Primary data were collected from private homes which supported elder care through observation and semi-structured interviews with primary family caregivers of the elderly. RESULTS: The study finds that the major factors preventing private homes from providing adequate care to the elderly were architecturally inadequate housing conditions, paucity of financial support, and scarcity of skilled caregivers. Besides, considerable neglect and domestic abuse of the elderly was also found in some private homes. In addition, the peripheral location of private homes within public health framework and inadequate state palliative policy, including stringent narcotic regulations, accentuated the problems of home care. CONCLUSION: The study concludes by questioning the rhetoric of private homes as spaces for the dying elderly in Kolkata and suggests remedial measures to improve their capacity to deliver care.